Technologies for Disabled - Nur Syazwanie Binti Dennis Emmanuel @ Mohd Dzulkiflee (IC-ITECHS, 2020)
No one asked to be born without a perfect physique. We cannot blame on the parent’s gene because mutation can be happened even though the parents are in a perfect health. For some unfortunate people, they have lost any part of their bodies, either their arms or their legs, or the ability to hear or speak after they met a tragic situation, whether from a horrible accident or facing mental health issue. Disabled people sometimes felt discouraged which led them into negative thinking and depression. That is why technologies for disabled are existed. There are wide range of technologies designed for these special people, which help them to have a perfect physique, seeing a nice sight and hearing beautiful sound. More outstanding athletes have been born because of the prosthetic, an assistive technology that widely used by athletes in Paralympic. Visually impaired or blind people can see better using a device named OrCam MyEye that enables them to read, to recognize faces, to identify products, and to provide a language support. People with hearing problem or deaf could live better because their hearing aids are provided with Bluetooth capability which can be connected to mobile phones and other devices with Bluetooth technology, often through an intermediary device. Furthermore, this new feature managed to overcome delayed sound problem. With these devices, disable people will able to stay in advances that have been going on in the world alongside with normal people.